Knowledge graph: A strategy for knowledge management? - Macedo , Valéria; Thurler , Larriza; Dias , Elaine; Cavalcanti , Marcos (Seven Editora, 2023)
This exploratory study sought to deepen the understanding of the benefits of using the knowledge graph technological solution for knowledge management. Through a bibliometric analysis of 45 academic articles selected from the Scopus database, with no time range determined, it was observed that the term has been addressed in academic productions on various topics with a greater number of publications from Asian researchers (71%). To understand the relationships of the keywords used by the authors of these articles, the VOSviewer tool was used to create the graph, making it possible to visualize the terms' clusters. It was identified that the theme is emerging, as the first article published in the Scopus database took place in 2011 and an expressive growth of publications can be observed in 2020. The production of academic knowledge with the use of the coupled knowledge graph stands out to the design of algorithms that support tutoring and curation activities with a focus on knowledge management in the areas of Health - including during the Covid-19 pandemic - and Education. The transversality of this solution is also noted, with studies using knowledge graphs in the areas of Engineering and Computer Science being observed. After further analysis, the authors selected 12 articles that presented initiatives focused on the area of Management and the use of the technological solution in activities aimed at intelligent recommendation can be observed, including the adoption of artificial intelligence and sampling algorithms for the study and development of solutions that resulted in the visualization of knowledge bases through the knowledge graph. The trend of using knowledge graphs for knowledge management pointed out by Knowledge Management (KM) World magazine can be found in business environments, such as Google and Wikipedia. It is believed that more empirical studies with knowledge graphs for knowledge management will be intensified in the digital age and this can be followed up in scientific congresses on the subject. DOI:https://doi.org/10.56238/sevened2023.006-041